The potential combination of noni (Morinda citrifolia) fruit extract and pandan (Pandanus amaryllifolius Roxb.) leaves extract as an anti-dandruff shampoo - Ambarwati Ambarwati; Tanti Azizah Sujono; Retno Sintowati (Wolters Kluwer Medknow Publications, 2021)
Aims: The study aimed to determine the inhibition activity of a combination of Noni fruit extract and Pandan leaves extract toward bacterial isolates that cause dandruff and to determine the potential of extract combination as an anti-dandruff shampoo. Subjects and Methods: The test bacteria were isolated from dandruff. The inhibition test of the extract combination was done by paper disc and well diffusion method. The identification of bacterial isolates was done in Balai Laboratorium Kesehatan Yogyakarta. Results: The study showed that the density of bacteria isolated from dandruff was 3.4 × 107 CFU/g. There were 28 pure bacteria isolates from purification process. The combination of Noni and Pandan extracts (1:1 v/v) could inhibit the growth of 92.9% bacterial isolates. There were seven species of bacteria from a total of 28 pure isolates, namely: Bacillus licheniformis, Bacillus megaterium, Bacillus alvei, Bacillus subtilis, Micrococcus sp, Stomatococcus sp, and Pseudomonas sp. Conclusions: Based on the research, it can be concluded that a combination of Noni fruit extract and Pandan leaves extract inhibited the growth of bacteria isolated from dandruff, so the combination of the extracts has potential as an anti-dandruff shampoo.